Effect of different concentrations of Taurine on certain physico -morphological attributes during cryopreservation of Gir bull semen - Chikhaliya, P S; Ahlawat , AR; Talekar , SH; Chaudhary , JK (Indian Journal of Dairy Science, 2022)
The study was carried out on four Gir bull (4-6 years) located at Cattle Breeding Farm J.A.U. Junagadh for a period of 6 weeks. Semen was collected using artificial vagina method once weekly for six weeks from each of the bulls A Total 8 semen sample from four healthy Gir breeding bulls were collected at weekly interval for two weeks period using of artificial vagina method for evaluation of semen biochemical attributes at various stages of cryopreservation of Gir bull semen. The semen was evaluated for physical characteristics at  per-freeze and post-thaw stages of cryopreservation using different Taurine concentrations viz. 25 mM Taurine, 50 mM Taurine, 75 mM Taurine and control was kept.At pre-freeze stages of cryopreservation, 50 mM Taurine group had value of 70.20 ± 1.22, 69.87 ± 3.09, percent for individual motility and  sperm viability, respectively, value were significantly (P